1997
DOI: 10.1128/iai.65.7.2517-2521.1997
|View full text |Cite
|
Sign up to set email alerts
|

Role of neutrophils in experimental septicemia and septic arthritis induced by Staphylococcus aureus

Abstract: We have previously described a murine model of hematogenously induced Staphylococcus aureus sepsis and arthritis. In this model, large numbers of granulocytes can be observed both in the circulation and locally in the inflamed synovium within 24 h after bacterial inoculation. To assess the role of neutrophils in this severe infection, mice were given granulocyte-depleting monoclonal antibody RB6-8C5 before being inoculated with S. aureus. All the control mice survived their intravenous injection with 3 ؋ 10 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(95 citation statements)
references
References 28 publications
2
91
1
1
Order By: Relevance
“…The ease with which conditional lineage ablation strategies can be applied to the zebrafish (Davison et al, 2007) suggests that this will be a valuable organism for these studies. Both neutrophils and macrophages appear to be important in mammals: neutropenic mice are highly susceptible to S. aureus infection in septic arthritis models, with S. aureus present in the bloodstream of neutrophil-depleted mice but not wild-type controls (Verdrengh and Tarkowski, 1997). Similarly, monocyte/macrophage-depleted mice are also more susceptible to S. aureus, giving higher bacterial numbers in blood than in control animals (Verdrengh and Tarkowski, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The ease with which conditional lineage ablation strategies can be applied to the zebrafish (Davison et al, 2007) suggests that this will be a valuable organism for these studies. Both neutrophils and macrophages appear to be important in mammals: neutropenic mice are highly susceptible to S. aureus infection in septic arthritis models, with S. aureus present in the bloodstream of neutrophil-depleted mice but not wild-type controls (Verdrengh and Tarkowski, 1997). Similarly, monocyte/macrophage-depleted mice are also more susceptible to S. aureus, giving higher bacterial numbers in blood than in control animals (Verdrengh and Tarkowski, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immune response is required for an efficient containment of S. aureus during a persistent infection We (von Köckritz-Blickwede et al, 2008) and others (Mölne et al, 2000;Verdrengh & Tarkowski, 1997) have shown that neutrophil recruitment is critical for effective control of bacterial growth during the acute phase of S. aureus infection. To determine their relevance for bacterial containment during the persistent phase, we depleted neutrophils in S. aureus-infected mice at day 28 p.i.…”
Section: Research Articlementioning
confidence: 99%
“…Staphylococci and their products are capable of strongly inducing various cytokines and are capable of activating cellular immunity. Cytokines including interferon-g (IFN-g), interleukin-4 (IL-4), IL-10 and IL-18 reportedly regulate host resistance against S. aureus infection (Nakane et al, 1995;Verdrengh & Tarkowski, 1997;Sasaki et al, 2000;Gomez et al, 2002). IFN-g-deficient mice, IFN-g receptor-deficient mice and IL-4-deficient C57BL/6 mice increased survival rates of S. aureus infection compared with that of wild-type mice, whereas the development of septicemia by S. aureus infection was inhibited in IL-18-deficient mice Hultgren et al, 1999;Wei et al, 1999;Sasaki et al, 2000).…”
Section: Introductionmentioning
confidence: 99%